Analisis Pemahaman Konsep Siswa pada Materi Fungsi Komposisi Ditinjau dari Gaya Belajar VAK - Tameon, Theresia Avila; Jagom, Yohanes Ovaritus; Gena, Margareta (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to analyze students' understanding of the concept of composite functions in terms of VAK (Visual, Auditory, and Kinesthetic) learning styles. The type of research used is descriptive qualitative with three subjects, namely 11th grade students of SMA Katolik Giovani Kupang, selected through purposive sampling. Data were collected using concept comprehension tests, learning style questionnaires, interviews, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing with triangulation of techniques and sources. The results of the study indicate that students with visual, auditory, and kinesthetic learning styles are able to restate concepts. However, subjects with visual and auditory learning styles are less careful in choosing work procedures and still make mistakes in algebraic calculations. Meanwhile, students with kinesthetic learning styles demonstrate better, more structured, and procedure-compliant conceptual understanding.